Evaluating efficacy of preoperative skin preparation with 2% chlorhexidine gluconate and 70% alcohol for reducing bacterial bioburden in dogs - Boonwittaya, Nithida; Yurayart, Chompoonek; Kaewmanee, Saroch; Duangurai, Taksaon (Agriculture and Natural Resources, 2025)
Importance of the work: Optimized antisepsis and protocols are essential for improving veterinary surgical outcomes and preventing surgical site infections (SSIs). Objective: To assess the effectiveness of 2% chlorhexidine gluconate and 70% alcohol (CHG-Alc) in reducing the bacterial bioburden, including multidrug-resistant strains, in canine surgical patients. Materials and Methods: A sample of 10 client-owned dogs was involved in the proposed standardized skin preparation protocol. Following an initial skin cleaning step, CHG-Alc was sprayed onto the skin and left in contact for 3 min. Then, the excess solution was gently removed. Bacterial cultures were collected at three time points: prior to antiseptic application (the first), immediately after the 3-min contact period and removal of the solution (the second) and 60 min after application (the third). Samples were processed to quantify bacterial load, identify bacterial species and assess antimicrobial resistance. Results: Pre-antisepsis, Staphylococcus pseudintermedius was the most frequently isolated bacterium, including the multidrug-resistant strains. Bacterial counts decreased significantly by over 99% at the second sampling time (p = 0.006), with complete absence of growth (0 CFU/mL) at the third sampling time (p = 0.006). Main Finding: CHG-Alc was highly effective for canine preoperative skin preparation, significantly reducing bacterial counts and preventing reinfection. There should be strong support for its use in veterinary preoperative protocols to minimize the risk of surgical site infections.